Community Financial Management Training to Create an Independent Prosperous Village - M. Nazori; Rafidah; Rosmanidar, Elyanti; Kusnadi, Dedek; Mutia, Agustina; Usdeldi; Fusfita, Nurlia; Subhan, Muhammad; Anita, Efni; Rahma, Sri; Nofriza, Eri; Alawiyah, Rabiyatul; Rahman, Sakinah (IJCS: International Journal of Community Service, 2024)
Financial management plays an important role in promoting independence and prosperity in communities, especially in rural areas where economic resources are often limited. This paper explores the importance of community financial management training as a catalyst for creating independent and prosperous villages. By equipping community members with important financial literacy skills, such as budgeting, savings, and investment strategies, villages can better manage their resources and increase their economic stability. This training focuses on empowering community leaders and residents to understand basic financial concepts and implement sustainable financial practices adapted to their local context. Through workshops, seminars, and practical exercises, participants learn to develop financial plans, identify potential sources of income, and reduce financial risks. In addition, this training emphasizes the importance of transparent financial governance and accountability to build trust and cooperation within the community. In addition, case studies and success stories from similar initiatives show the positive impact of financial management training on village development. These examples illustrate how better financial decision making can lead to increased household income, better infrastructure development, and higher social welfare. Ultimately, the goal is to create self-sufficient villages that can develop independently by utilizing their resources effectively and responsibly.